Immunopathogenesis of Human Sporotrichosis: What We Already Know - Silva, Fátima Conceição (2018)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Imunoparasitologia. Rio de Janeiro, RJ. Brasil.